EVALUASI IMPLEMENTASI NILAI-NILAI SYARIAH DALAM SISTEM PELAYANAN NASABAH PADA BANK SYARIAH INDONESIA KC BOJONEGORO - Isnaini Anniswati Rosyida (Jurnal Pengabdian kepada Masyarakat, 2026)
This community service project aims to evaluate the implementation of sharia values ​​in the customer service system at Bank Syariah Indonesia Bojonegoro Branch, by positioning the service experience as a space where values ​​are not only understood but also implemented. The approach used was descriptive qualitative through observation, in-depth interviews, and documentation. The results of the community service show that sharia values ​​such as ṣidq (honesty), amanah (responsibility), tabligh (transparency), and fathanah (competence) have been attempted in service practices, particularly in polite communication and openness of information to customers. However, this implementation has not been fully consistent, especially in busy service conditions, where efficiency orientation tends to be more dominant than the appreciation of values. These findings indicate that sharia values ​​have been present as formal guidelines and have begun to shape the service identity, but have not yet fully become an ingrained culture. Therefore, strengthening the aspect of internalization of values ​​through continuous development is needed, so that sharia principles are not merely procedural, but truly become the spirit of every service to customers.